Morphometric Characterisation of Ongole-Grade Cattle from a Breeding-Source Area: Baseline Phenotypes to Support Selection and On-Farm Conservation - Doni Herviyanto; Veronica Margareta Ani Nurgiartiningsih; Kuswati Kuswati; Marjuki Marjuki; Ifar Subagyo; Sucik Maylinda; Priyo Sugeng Winarto (Buletin Peternakan, 2026)
Ongole-grade cattle are a major locally adapted beef resource in Indonesia, yet breeding-source village populations often lack quantitative baseline phenotypes to support objective selection and on-farm conservation. This study characterised age-standardised morphometric traits of Ongole-Grade cattle from the breeding-source population in Napis Village (Bojonegoro, East Java). A cross-sectional survey was conducted on 356 clinically healthy cattle (143 males and 213 females) aged 24–48 months. Twelve linear measurements were recorded (withers height, body length, chest girth, chest depth, rump height, rump width, cervical/thoracic/lumbar vertebral lengths, scapula length, head length and head width) and standardised to 24 months using allometric size correction prior to analysis. Sex effects were tested using one-way ANOVA and Tukey comparisons, and principal component analysis (PCA) was performed separately by sex on z-standardised traits. All traits differed between sexes (p ≤ 0.002). Males were larger for most frame and head/axial traits (e.g., withers height, body length, chest depth, rump height, cervical and lumbar vertebral lengths, scapula length, head length and head width; p < 0.001), whereas females were larger for rump width, chest girth and thoracic vertebral length (p ≤ 0.002). PCA revealed a consistent conformation structure in both sexes, with PC1 representing a general size axis (47.3% variance in males; 42.7% in females) and PC2 capturing proportionality (shape), increasing cumulative explained variance to 70.8% in males and 64.5% in females. These results provide population-specific morphometric references and multivariate descriptors that can strengthen selection criteria and recording schemes for Ongole-Grade cattle in breeding-source village systems.